2018
DOI: 10.1002/ece3.4168
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic‐induced effects on scaling relationships and on plant element contents in herbs and grasses

Abstract: Plant performance is correlated with element concentrations in plant tissue, which may be impacted by adverse chemical soil conditions. Antibiotics of veterinary origin can adversely affect plant performance. They are released to agricultural fields via grazing animals or manure, taken up by plants and may be stored, transformed or sequestered by plant metabolic processes. We studied the potential effects of three antibiotics (penicillin, sulfadiazine, and tetracycline) on plant element contents (macro‐ and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…The successful application of antimicrobials has significantly increased the production and use of antimicrobials ( Tiseo et al, 2020 ; Tian et al, 2021 ). Some intensively used antimicrobials interrupt mitochondrial proteostasis and physiology in animals ( Wang et al, 2015 ) and also impact plant chloroplasts in terrestrial and aquatic plants ( Carvalho et al, 2014 ; Minden et al, 2018 ); thus, they affect the ecosystems and biogeochemical processes ( Zhou et al, 2021 ). FLO is widely used in veterinary clinics and aquaculture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The successful application of antimicrobials has significantly increased the production and use of antimicrobials ( Tiseo et al, 2020 ; Tian et al, 2021 ). Some intensively used antimicrobials interrupt mitochondrial proteostasis and physiology in animals ( Wang et al, 2015 ) and also impact plant chloroplasts in terrestrial and aquatic plants ( Carvalho et al, 2014 ; Minden et al, 2018 ); thus, they affect the ecosystems and biogeochemical processes ( Zhou et al, 2021 ). FLO is widely used in veterinary clinics and aquaculture.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria and chloroplasts have bacterial-type ribosomes because they are evolved from endosymbiotic α-proteobacteria and cyanobacteria-like prokaryotes, respectively ( Ferrari et al, 2021 ); this condition makes these organelles vulnerable to ribosome-targeted antimicrobials ( Wang et al, 2015 ). Increasing numbers of studies show that some intensively used antimicrobials disturb mitochondrial proteostasis and physiology in animals ranging from worms, fruit flies, and mice to human cell lines ( Wang et al, 2015 ), and they also impact plant chloroplasts, inducing toxic effects on terrestrial and aquatic plants ( Carvalho et al, 2014 ; Minden et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, both plants showed that the drug accumulated mainly in the roots and to a lesser extent in the green parts, confirming that these compounds were uptaken from the environment. Studies conducted on herbs and grasses treated with penicillin, sulfadiazine and tetracycline confirmed that the roots were most strongly affected by FCs compared to the steams and leaves [ 13 ]. Additionally, the presence of FCs in the soil disrupted homeostasis in the plant body, reduced the elemental content of the plant and led to salt stress.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the effects of antibiotics vary from antibiotic to antibiotic and also vary by plant species. Minden et al indicated that antibiotics can affect element contents in plants [ 15 ]. Chen et al [ 16 ] showed that oxytetracycline exposure diminished the photosynthetic capacity of rape.…”
Section: Introductionmentioning
confidence: 99%